MASCULINITY ON THE AFRICAN CONTINENT - Eagle, Gillian (PINS-Psychology in Society, 2025)
Ouzgane, L and Morrell, R (eds) (2005) African masculinities: Men in Africa from the late nineteenth century to the present. Pietermaritzburg / New York: University of KwaZulu-Natal Press / Palgrave Macmillan. ISBN 1-86914-063-X pbk. Pages vii + 308. This, somewhat ambitious, text makes an unusual contribution to the field of masculinity studies by engaging specifically with masculinity as it is lived, constructed and depicted on the African continent. As the authors point out in the introduction to the text, the aim of the book is twofold: firstly to “address the subject of masculinities in Africa” and secondly to “apply the concepts of critical men’s studies to the analysis of masculinities on the continent” (Morrell & Ouzgane, 2005:1). The book delivers on both intentions and offers a very diverse range of contributions on these two topics. Much of the material is framed within a post-structuralist or post-colonial theoretical frame and readers familiar with such kinds of conceptualization may find the material easier to read than those unfamiliar with this kind of social science scholarship. The authors include both African and other (American and European) scholars, all working on different subject matter relating to African masculinity. The writing describes the experiences of men and women and aspects of gender relations across a number of African countries, including Egypt, Nigeria, Zambia, Mocambique, Botswana and South Africa, recognizing that manifestations and expressions of masculinity are historically located and in many respects, culture specific. Although it appears that attempts were made to be as inclusive as possible, clearly some countries are better represented than others. For example, there are quite a number of contributions on or from South Africa, probably because of the familiarity of Morrell with scholarship in this country.